Dissecting the Genetic Basis for Seed Coat Mucilage Heteroxylan Biosynthesis in Plantago ovata Using Gamma Irradiation and Infrared Spectroscopy - Tucker, Matthew R.; Ma, Chao; Phan, Jana; Neumann, Kylie; Shirley, Neil J.; Hahn, Michael G.; Cozzolino, Daniel; Burton, Rachel A. (Frontiers in Plant Science, 2017)
Seeds from the myxospermous species Plantago ovata release a polysaccharide-rich mucilage upon contact with water. This seed coat derived mucilage is composed predominantly of heteroxylan and is utilised as a gluten-free dietary fibre supplement to promote human colorectal health. In this study, a gamma-irradiated P. ovata population was generated and screened using histological stains and Fourier Transform Mid Infrared (FTMIR) spectroscopy to identify putative mutants showing defects in seed coat mucilage heteroxylan composition and/or structure. FTMIR analysis of dry seed revealed variation in regions of the IR spectra previously linked to xylan structure in Secale cereal (rye). Subsequent absorbance ratio and PCA multivariate analysis identified 22 putative mutant families with differences in the heteroxylan IR fingerprint region. Many of these showed distinct changes in the amount and subtle changes in structure of heteroxylan after mucilage extrusion, while 20% of the putative heteroxylan mutants identified by FTMIR showed no difference in staining patterns of extruded mucilage compared to wild-type. Transcriptional screening analysis of two putative reduced xylan in mucilage (rxm) mutants, rxm1 and rxm3, revealed that changes in heteroxylan levels in rxm1 correlate with reduced transcription of known and novel genes associated with xylan synthesis, possibly indicative of specific co-regulatory units within the xylan biosynthetic pathway. These results confirm that FTMIR is a suitable method for identifying putative mutants with altered mucilage heteroxylan composition in P. ovata, and therefore forms a resource to identify novel genes involved in xylan biosynthesis.